2017
DOI: 10.1002/adhm.201601291
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Development of Methods for Characterization of Microspheres for Use in Embolotherapy: Translating Bench to Cathlab

Abstract: Microspheres in Advanced Healthcare ApplicationsMicrospheres are small spherical particles with a diameter in the range 1-1000 µm, typically free-flowing in nature that can be made from either synthetic or natural materials (or a combination thereof). They have found widespread use in healthcare applications because numerous methods exist to manufacture Therapeutic embolotherapy is the deliberate occlusion of a blood vessel within the body, which can be for the prevention of internal bleeding, stemming of flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 133 publications
1
67
0
Order By: Relevance
“…A spherical microgel morphology is ideal for several applications: spherical particles (i) conformally embed suspended cells, thereby providing isotropic 3D biochemical and biophysical stimuli; (ii) result in less clogging compared with irregularly shaped microparticles, which, for example, enables injection of higher microgel concentrations using thinner needles [87]; (iii) cause less intense inflammatory responses upon in vivo implantation [88]; and (iv) intrinsically form predictable and well-controlled interconnected networks upon stacking, which promotes solute diffusion and tissue ingrowth (e.g., vascularization) [85].…”
Section: Box 2 the Advantages Of A Spherical Microgel Morphologymentioning
confidence: 99%
“…A spherical microgel morphology is ideal for several applications: spherical particles (i) conformally embed suspended cells, thereby providing isotropic 3D biochemical and biophysical stimuli; (ii) result in less clogging compared with irregularly shaped microparticles, which, for example, enables injection of higher microgel concentrations using thinner needles [87]; (iii) cause less intense inflammatory responses upon in vivo implantation [88]; and (iv) intrinsically form predictable and well-controlled interconnected networks upon stacking, which promotes solute diffusion and tissue ingrowth (e.g., vascularization) [85].…”
Section: Box 2 the Advantages Of A Spherical Microgel Morphologymentioning
confidence: 99%
“…Therapeutic utility of embolic bodies is further enhanced with the design of DEB, specifically using hydrogel biomaterials. The use of hydrogels in these systems is advantageous over “solid” beads in that hydrogels are soft, nondamaging to the vasculature, and can adapt their shape for deeper penetration into the vascular bed . Commercially available embolic beads (e.g., DC Beads) are based on poly(vinyl alcohol), a polymer which we have previously used for the development of EPT in the context of implantable biomaterials .…”
Section: Resultsmentioning
confidence: 99%
“…6,7 Therefore, the performance of the chemoembolization vectors is the key determinant of TACE outcome. [8][9][10] The major goal of TACE is to achieve complete tumor necrosis, thus providing patients with survival benefits as much as possible. It has been demonstrated that the magnitude of tumor necrosis, in terms of treatment response which is usually assessed by contrast enhanced imaging studies, correlated closely with prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…DEB release per loaded drugs via ion-exchange mechanism in a slow and sustained release pattern to deliver chemotherapeutic agents toward tumor lesions continuously. [8][9][10] However, being intrinsically drug-resistant in nature, liver cancer is notorious for being refractory to either systemic or transarterial infusion chemotherapy. 4,16 Furthermore, conclusive evidence supporting the superiority of TACE over transarterial embolization (TAE) is still absent, suggesting the poor performance of chemotherapy for liver cancer.…”
Section: Introductionmentioning
confidence: 99%